COVID-19 pandemic: An outlook on its impact on air quality and its association with environmental variables in major cities of Punjab and Chandigarh, India. Issue 1 (3rd April 2021) - Sahoo, Prafulla Kumar; Chauhan, Amit Kumar; Mangla, Sherry; Pathak, Ashok Kumar; Garg, V. K.
Abstract: The present study aims to evaluate the impact of COVID-19 lockdown on air quality and to explore the association of daily COVID-19 confirmed cases with meteorological parameters and criteria pollutants in the major cities of Punjab and Chandigarh, India during the different phase of pre-lockdown (March 1 to March 24), lockdown (1.0, 2.0, 3.0, 4.0; March 25 to May 31), and unlock (1.0, 2.0; > June 1) in 2020. Our results show that the COVID-19 lockdown has drastically improved the quality of air in major cities of Punjab and Chandigarh. Compared to pre-lockdown, maximum reduction of PM2.5 and PM10 levels (up to −52 and −53.5%, respectively) was witnessed during lockdown 1.0, but their levels were rising again during the last phase of lockdown and unlock phases. This is due to more relaxation and traffic returned on the road. Among other pollutants, NO2 also reduced during lockdown 1.0, but remained variable between cities and different phases of lockdown and unlock periods. However, surface-level ozone resulted in an overall increase trend during the lockdown and unlock phases. Regarding the relationship between COVID-19 and meteorological parameters, Spearman correlation test shows that ambient temperature is positively correlated with COVID-19 daily confirmed cases ( r < 0.77, p < 0.01). This result indicates that the study region's hot tropical weather is less effective in controlling the spread of COVID-19. Relative humidity and wind speed are also weakly correlated with COVID-19. Furthermore, among criteria pollutants, PM2.5 and PM10 are positively correlated ( r < 0.55, p < 0.01) with COVID-19 pandemic, especially in Jalandhar and Ludhiana, suggesting that these pollutants could lead to the spreading of the virus. However, further in-depth studies are required to validate this finding. The results of this study can contribute to the understanding of the role of environmental factors in the transmission of COVID-19 in tropical and sub-tropical countries like India, Brazil, etc. This study also indicates that the temporary lockdown like COVID-19 can be emerged as an effective way to control environmental imbalance in the study area, as well as in other areas.